Data on vegetation composition, soil edaphic variables and fungal communities in 1-13 year old clearcuts in central Sweden - Boeraeve, Margaux; Granath, Gustaf; Lindahl, Björn D.; Clemmensen, Karina E.; Strengbom, Joachim (Swedish University of Agricultural Sciences, 2025)
Data collected from clearcuts, 1 to 13 years after clearcutting, in central Sweden (Uppland and Västmanland). It contains data on the vegetation composition, height and growth rate of trees, soil organic layer carbon and nitrogen stocks, enzyme activities in the soil organic layer (for only a part of the samples) and the soil fungal communities.

Data från kalhyggen, 1 till 13 år efter avverkning, i Mellansverige (Uppland och Västmanland). Det innehåller uppgifter om vegetationens sammansättning, trädens höjd och tillväxt, kol- och kväveförråd i markens organiska skikt, enzymaktiviteter i markens organiska skikt (endast för en del av proverna) och svampsamhällen i marken.
Data om vegetationen, markkol och kväve och svampsamhällen på 1-13-åriga hyggen i Mellansverige
Keywords: Soil; Mark; Species distribution; Arters utbredning; carbon cycle; kolets kretslopp; forest vegetation; skogsvegetation; mycorrhizal fungi; mykorrhizasvampar; soil respiration; markandning; clearcuttings; kalhyggen; forest fertilisation; skogsgödsling; Pinus sylvestris; tall; Picea abies; gran; Betula; björkar; Ericales; ljungordningen; Fungi; svampar; Ecology; Ekologi; Environment; Miljö